Policies for optimal nutrition-sensitive options: a study of food and nutrition security policies, strategies and programs in Ghana, Kenya and South Africa - Sibanda, Simbarashe; Munjoma-Muchinguri, Pamela; Ohene-Agyei, Phyllis; Murage, Alice Warukira (Frontiers in Sustainable Food Systems, 2023)
Sub-Saharan Africa is experiencing the coexistence of overnutrition, undernutrition and micronutrient deficiencies. Comprehensive programs and coherent public policies are required to address this problem. A study of food and nutrition security policies, strategies and programs in Ghana, Kenya and South Africa was conducted between February and July 2022 through desk reviews and key informant interviews. The aim was to generate evidence on the extent to which the policies, strategies and programs were nutrition-sensitive and add value to the scaling up of nutrition and food security. The assessment of the documents was based on the four dimensions of food security, and the Food and the Food and Agriculture Organization of the United Nations guidelines on nutrition-sensitive agriculture. A total of 48 policies, strategies and programs were reviewed. To ensure food availability, most reviewed documents tend to focus on food production and income generation, with limited attention on production and supply of diverse and nutrient-dense foods. Access to inputs, credit and land is targeted at smallholder farmers, without little sensitivity to women and youth engagement. Food access is promoted through improved market access by upgrading infrastructure and promoting social safety nets for vulnerable populations. However, information systems for agricultural marketing as well as labor- and time-saving technologies are lacking. Although nutrition education is widely promoted, especially for mothers and children, there is a gap in addressing the nutrition needs of adolescent girls. Regarding food stability, inadequate funding, poor leadership and governance and inadequate monitoring and evaluation systems are the main barriers to successful implementation of policies, strategies and programs. While efforts have been made to promote nutrition-sensitive options in the agriculture and food system value chains, the study identified several gaps that need to be addressed to ensure adequate food and nutrition security.